Peran Elit Desa dalam Partisipasi di Tingkat Lokal dalam Perumusan Musrembang di Desa Blahbatuh Kabupaten Gianyar - Mantrawan, I Putu Wahyu; Noak, Piers Andreas; Erviantono, Tedi (Jurnal Nawala Politika; 2016, 2016)
ABSTRACT This research is motivated by the position and the role of the village elite in influencing the formulation musrenbang in Gianyar Blahbatuh village. Non government elite into a figure capable of mobilizing the community so as to create social dynamics that will affect resultant force on the formulation of policies between the ruling elite and the local elite in the village Blahbatuh. The purpose of this study seeks to dissect the participation of the local community to the village elite in relation to the formulation musrenbang Blahbatuh village. This study uses qualitative research methods - the descriptive study using a model of Bungin. Engineering research data collection is done by direct observation, and literature that have relevance to the theme of the research as well as assign a resource by interviewing community leaders non - government and aperture Blahbatuh villages and rural communities. The research proves that the villagers Blahbatuh have a high level of political consciousness it is proved that the village administration is part of the local community so that the synergy between the government, the elite non - government and community berasas democratic, rational, interactive and transparent. Local elites non - government became an influential figure in the formulation typically musarembang not only suggest policy proposals alone but actively conduct political lobbying in policy development processes as well as determine the direction of policy. Keyword: Musrenbang, Elit, Society